A STUDY ON ASHA –A CHANGE AGENT OF THE SOCIETY - Saxena, Vartika; Kakkar, Rakesh; Semwal, V D (Indian Journal of Community Health, 2012)
Background: National Rural Health Mission started in the state of Uttarakhand with the objective to address the health needs of rural population, especially the vulnerable section of the society. Under this scheme, ASHA has been identified as one of the key strategy for wider coverage of services, considering her the first port of call for any health related demands, especially women and children. Objective: To find out the biosocial profile of ASHA and services provided by them. Material & Methods: A descriptive study was conducted in Imlikhera Block of Haridwar district in 2008 participated by all (150) ASHA. Data was collected by trained investigators of Rural Development Institute which is also a State ASHA resource Centre. Results: Maximum (42%) ASHA were in 26-30 Years of age group. However, 23% ASHA were in less than 25 years of age which is below than the stipulated selection criteria. About 6.3% ASHAs were not fulfilling the educational criteria of selection (education upto 8th class). Study reported that majority of ASHA consider care of pregnant women, vaccination and family planning as their prime services. 42% ASHA reported that they think this work can pave their ways for future employment. Conclusion: Supervisory body should see that selection of ASHA should be as per stipulated criteria and they should be sensitized about their major role of motivator & activist, for creating awareness and demand generation in the society.